The Effect of Corporate Governance on Environmental Disclosure and Its Impact on the Financial Performance of Sharia Mining Companies in Indonesia - Adetiya Sabrina M. Nur; Muhamad Umar Mai; Dian Imanina Burhany (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
Mining companies provide a large added value to the economy, but their operational activities also cause a large environmental impact. The balance of the company's relationship with stakeholders including those related to the environment is something that needs to be maintained because it will have an impact on financial performance. Therefore, companies must apply corporate social responsibility (CSR) in particular for environmental aspects and express them. Corporate governance is the determining factor of environmental disclosure. So this research was conducted with the aim of examining the influence of the elements corporate governance which consists of the size of the board of commissioners, the proportion of female commissioners, the proportion of independent commissioners, and the size of the audit committee to environmental disclosure, and its impact on the financial performance of companies in the sharia mining sector. The basis of sharia is considered to be in favor of environmental sustainability. This research is a quantitative study with a sample of sharia mining companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The research data is secondary data sourced from annual reports and corporate sustainability reports. Data analysis using SEM-PLS. The results of the study show that the size of the board of commissioners and the proportion of female commissioners have an effect negative to environmental disclosure while the proportion of independent commissioners and the size of the audit committee has no effect on environmental disclosure. Furthermore, environmental disclosure has an effect on financial performance for return on assets (LONG)